Diversity, vertical structure and floristic relationships of vascular epiphytes in an urban remnant of the Brazilian Atlantic Forest - Santana,Lucas Deziderio (2017)
ABSTRACT This study was conducted in a fragment of montane seasonal semi-deciduous forest (Minas Gerais State) with a history of anthropogenic disturbance. Our goals were to characterise the composition, structure and floristic diversity of vascular epiphytes and to investigate the floristic similarities of the community with other areas of urban seasonal forests in Brazil. We sampled 61 phorophytes with 47 epiphytic species. The richest families were Bromeliaceae (seven) and Polypodiaceae (seven). The most common ecological category was accidental holoepiphytes with 21 species - an unprecedented result for the Neotropical region. The Shannon index was 2.95 and the Pielou evenness index 0.77, showing a relatively high diversity with a few dominant species and numerous rare species. Similarity analyses showed a longitudinal gradient and strong influence of the distance from the ocean on floristic relationships as well as influence of dense ombrophilous forests on the composition of the vascular epiphytes of the surveyed area.